Effect of Exogenous Melatonin on Postharvest Storage Quality and Softening-related Gene Expression of Prunus domestica - Pei QIAO; Huixing LI; Jiancheng LUO; Shuang CHENG; Haiyan YU (Shipin gongye ke-ji)
Objective: This study investigated the effects of exogenous melatonin treatment on the post-harvest quality and related metabolism of postharvest prune fruits. Methods: The Sichuan Guang'an prunes fruit with 60, 120 and 240 μmol/L melatonin (MT) were treated as the treatment groups, and water treatment was treated as the control group in this study. The changes in storage quality and related metabolism of prunes fruit including color, weight loss rate, total soluble solid content (TSS), soluble protein content, cell membrane permeability and malondialdehyde (MDA) content were observed during room temperature (22±3 ℃, 65%±5% RH) storage. Results: In terms of fruit color, there was no significant difference in L* and b* values between different MT treatment groups and the control group (P>0.05), while c* values showed significant differences in the later stage of storage (9~12 days) (P<0.05), with the 60 and 120 μmol/L MT treatment groups showing the most significant differences compared to the control group. In terms of storage quality, during the later stages of storage (6~12 days), the increase in weight loss rate was inhibited significantly in different MT treatment groups relative to the control group (P<0.05), with the 60 μmol/L treatment group showing the best effect. At the same time, different MT treatment groups were able to effectively inhibit the decrease in TSS content relative to the control group (P<0.05), with the 240 μmol/L treatment group showing the best effect.While the decrease in TSS content inhibited effectively in different MT treatment groups compared to the control group (P<0.05), with the 240 μmol/L treatment group showing the best effect. Regarding the cell membrane structure of prunes fruit, the increase of cell membrane permeability and MDA content were inhibited effectively in different treatment groups of prunes fruit during the mid storage period (3~9 days) compared to the control group (P<0.05), with the 60 μmol/L treatment group showing the best effect. Regarding the metabolism of reactive oxygen species in prunes fruit, different treatment groups were found to effectively promote the increase of superoxide dismutase (SOD) and peroxidase (POD) enzyme activities during the late storage period (9~12 days) compared to the control group (P<0.05), with the 60 μmol/L treatment group showing the best effect. Regarding softening related metabolism, compared to the control group, the activities of polygalacturonase (PG), β-galactosidase (β-Gal), and cellulase (Cx) were all inhibited in different MT treatment groups, as well as the relative expression increase in the expression levels of PdPG2, PdCx6 and Pdβ-GAL3. The expression level of PdPME31 was effectively maintained, but there was only a significant difference between the 60 μmol/L MT group and the CK group (P<0.05), while there was no significant difference between the 120 and 240 μmol/L MT treatment groups (P>0.05). Finally, after principal component analysis, it was found that the 60 μmol/L MT treatment had better preservation effect compared to the 120 and 240 μmol/L MT treatments. Conclusion: Exogenous MT treatment can effectively regulate the activity of softening related enzymes and the expression levels of related genes, delaying fruit softening during storage. On the other hand, it increases antioxidant enzyme activity, reduces the damage of reactive oxygen species to cell membrane structure, and ultimately achieves the goal of delaying the shelf life of post harvest plum fruit. The research results provide a theoretical basis for the application of exogenous melatonin in post-harvest fruits and vegetables.